2006
DOI: 10.1039/b505518k
|View full text |Cite
|
Sign up to set email alerts
|

Differential receptor arrays and assays for solution-based molecular recognition

Abstract: Nature has inspired an emergent supramolecular field of synthetic receptor arrays and assays for the pattern-based recognition of various bioanalytes and metal species. The synthetic receptors are not necessarily selective for a particular analyte, but the combined signal response from the array is diagnostic for the analyte. This tutorial review describes recent work in the literature for this emerging supramolecular field and details basic array and assay design principles. We review the analytes targeted, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
246
0
7

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(253 citation statements)
references
References 34 publications
0
246
0
7
Order By: Relevance
“…In fact patter recognition using chromogenic differential receptors has become an active research field in the last years. 91 In this example the authors developed an array of complex-dye ensembles to test the potential detection of certain carboxylates. 92 As sensing systems the authors combined ligands 50-58 ( Figure 17 The same research group used a similar concept for the differential recognition of small peptides and their phosphorylated analogues.…”
mentioning
confidence: 99%
“…In fact patter recognition using chromogenic differential receptors has become an active research field in the last years. 91 In this example the authors developed an array of complex-dye ensembles to test the potential detection of certain carboxylates. 92 As sensing systems the authors combined ligands 50-58 ( Figure 17 The same research group used a similar concept for the differential recognition of small peptides and their phosphorylated analogues.…”
mentioning
confidence: 99%
“…The specific interactions involved between the reporter elements and the analyte are noncovalent and reversible. This approach provides an alternative to ''lock-key'' specific recognition (24) and has been used to detect metal ions (25), volatile agents (26), aromatic amines (27), amino acids (28,29), and carbohydrates (25). In recent research we have demonstrated that the displacement of fluorescent polymers from differentially functionalized gold nanoparticles with concomitant restoration of fluorescence provides an effective array-based method for the identification of proteins (30).…”
mentioning
confidence: 99%
“…As línguas e narizes dos mamíferos, repletos de arranjos de receptores "diferenciais" para o paladar e o olfato, 130,147 têm inspirado o conceito de arranjos de receptores diferenciais sintéticos, 130,132,148 que transcendem a relativa falta de especificidade para determinados analitos pela geração de impressões digitais que cada analito deixa ao ficar em contato com o arranjo. Aqui também são necessárias as mesmas estratégias de reconhecimento usadas para os quimiossensores individuais.…”
Section: Perspectivasunclassified
“…Entretanto, os padrões de aquisição de dados e de interpretação dos padrões de reconhecimento são diferentes, necessitando agora estarem fortemente ancorados em ferramentas qui mio métricas. 130,148,149 Elas são fundamentais para a geração e interpretação das impressões digitais por parte de cada analito presente no sistema sob análise, o que permite obter respostas às interrogações feitas sobre misturas complexas. Essa estratégia combinada leva à detecção simultânea de vários analitos e esse conceito tem revolucionado a concepção das línguas eletrônicas, 150 dispositivos para a análise simultânea de múltiplos analitos em solução, e narizes eletrônicos, 124,151 para analisar simultaneamente analitos múltiplos em fase gasosa.…”
Section: Perspectivasunclassified